New inextensible flows of principal normal spherical image - Körpınar, Talat (WORLD SCIENTIFIC PUBL CO PTE LTD, 2018)
In this work, we study normal spherical indicatrices (images) in terms of inextensible flows in E-3. We discuss the geometric properties of the normal spherical indicatrices. Furthermore, we give some new characterizations of curvatures in terms of some partial differential equations in E-3.
Keywords: Fluid flow; E-3; partial differential equation; spherical indicatrices